2018
DOI: 10.1016/j.jmatprotec.2018.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and FE analysis of void closure in hot rolling of stainless steel

Abstract: Casting metal products are characterized by undesired void defects due to the shrinkage occurring during the solidification of molten material. In order to deliver safe and sound components satisfying the customer requirements, these defects need to be reduced or if possible eliminated. Hot metal forming processes can be used for this purpose therefore, the calibration of their parameters is a fundamental task. In this paper a study of the void closure during hot rolling of 316L stainless steel slabs coming fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In caliber rolling, damage evolves at elevated temperatures, where the microstructure undergoes constant changes due to recrystallization and recovery during plastic flow, which could influence the damage evolution at microscopic scale. For instance, existing voids can be healed due to recrystallization, as described by Wang et al [10] and Faini et al [11]. To study the effect of non-proportional loading path at elevated temperature, the evolution of microstructure needs to be considered and its effect should be ideally separated from that of the loading path.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…In caliber rolling, damage evolves at elevated temperatures, where the microstructure undergoes constant changes due to recrystallization and recovery during plastic flow, which could influence the damage evolution at microscopic scale. For instance, existing voids can be healed due to recrystallization, as described by Wang et al [10] and Faini et al [11]. To study the effect of non-proportional loading path at elevated temperature, the evolution of microstructure needs to be considered and its effect should be ideally separated from that of the loading path.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…Nalawade et al [ 28 ] studied the effect of temperature, rolling torque, and void volume fraction on void closure during hot rolling. Faini et al [ 29 ] also studied void closure using hot‐rolling simulations for steel material and obtained a correlation with percentage reduction, cooling time, and location of void. It is observed that high temperatures, compressive stresses, and diffusion help in crack healing and induce closure.…”
Section: Introductionmentioning
confidence: 99%
“…The third approach involves using direct industrial installation to analyse defect evolution. Faini et al [20] used this approach to evaluate a multistage rolling process of long products by comparison with FEM analysis. In this modelling, the Q factor and the effective strain level are used to evaluate the forming route capacity with regard to defect closure.…”
Section: Introductionmentioning
confidence: 99%